Mycobiology of Dental Unit Water: A Systematic Scoping Review - Norbert Soboń; Kausar Sadia Fakhruddin; Lakshman Samaranayake; Nabiha Belkacem Remmani; Marwan Mansoor Mohammed; Thantrira Porntaveetus (International Dental Journal)
Fungi present in Dental Unit Water (DUW) can pose a health hazard to patients and dental personnel. Yet, the issue of fungal contamination of DUW and their conduits, DUW Lines (DUWLs) has been poorly addressed despite a growing body of data on the subject. In this comprehensive review, we aim to address this gap by examining the diverse fungal contaminants found in DUW, the challenges associated with controlling their growth within waterline biofilms, and the various measures employed for fungal decontamination. The review underscores the intricate fungal ecosystems that exist within DUWLs and emphasizes the importance of implementing targeted antimicrobial strategies to uphold waterline hygiene. However, it is important to note that complete eradication of fungi in DUWLs has proven elusive, even with the application of disinfectants at varying concentrations, types, and frequencies. This highlights the pressing need for continued research efforts to develop new and optimized treatment protocols that are specifically tailored to eradicate fungi from DUWLs. Finally, it was notable that there are currently no specific regulations by any dental authority on permissible levels of fungi, as opposed to bacteria, in DUWLs. Legislation developed based on our findings can contribute to the standardization of practices and the formulation of effective control strategies for fungal contamination in DUWLs. It can also guide dental professionals in implementing regular monitoring, proper maintenance, and targeted disinfection protocols to minimize fungal contamination and ensure optimal water quality for patient safety.